PEMBERIAN BENZIL AMINO PURIN (BAP) TERHADAP EKSPLAN ADENIUM (Adenium obesum) SECARA IN VITRO - Faturrahman Faturrahman; Melisa Melisa; Selvia Sutriana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
Application of Benzyl Amino purine (BAP) to Adenium (Adenium obesum) explants in vitro was conducted at the laboratory of Biotechnology, Faculty Agriculture Islamic University of Riau. This research aims to examine the response of 2 (two) sources of explants material Adenium plant (Adenium obesum). The Completely Randomized Design was used under factorial, consisting two factors: the first factor is the use of explants with two treatment levels, namely: E1 = the use of adenium stem explants and E2 = the use of adenium shoot tip explants. The second factor is the BAP with four treatment levels, namely: B0 = Without BAP (control), B1 = BAP concentrations of 0.1 mg / l, B2 = BAP concentrations of 1.0 mg / l, B3 = BAP concentrations of 10 mg / l. The results show that the treatment had no a significant effect of interaction, but the treatment E2B2 BAP (bud explants with BAP 1 mg /l) showed the highest response to the growth of explants compared to other treatment interactions. The BAP alone on adenium explant response, especially in treatment B2 (BAP 1 mg / l medium). Best explant types obtained were derived from the shoot tip, showing significant effect on the percentage of shoots formation.